2014
DOI: 10.1007/s11095-014-1454-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-Spray Dried Carbohydrate Microparticles: Crystallisation Delay/Inhibition and Improved Aerosolization Characteristics Through the Incorporation of Hydroxypropyl-β-cyclodextrin with Amorphous Raffinose or Trehalose

Abstract: The co-spray drying of raffinose or trehalose with HPβCD results in powders with improved physicochemical characteristics, physical stability and aerodynamic behaviour compared to spray-dried raffinose/trehalose particles, constituting improved potential drug-carrier systems for pulmonary delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…These events are believed to occur as a results of partial amorphous IBU collapsing into its crystalline stableform, as crystalline phases are less hydrophilic than amorphousones. Similar studies were reported elsewhere (Amaro et al, 2015). Excessive amount of PEG (12% w/w) present in the formulation F11 may have played a vital role for this event while F2 and F10 both have lesser amount in the formulations.…”
Section: Dvs Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…These events are believed to occur as a results of partial amorphous IBU collapsing into its crystalline stableform, as crystalline phases are less hydrophilic than amorphousones. Similar studies were reported elsewhere (Amaro et al, 2015). Excessive amount of PEG (12% w/w) present in the formulation F11 may have played a vital role for this event while F2 and F10 both have lesser amount in the formulations.…”
Section: Dvs Analysissupporting
confidence: 86%
“…The DVS Advantage-1 uses a Cahn D200 recording ultramicrobalance with a mass resolution of ±0.1 μg; the vapour partial pressure around the sample is controlled by mixing saturated and dry carrier gas streams (N2) using electronic mass flow controllers (Amaro et al, 2015). Samples were equilibrated at 0% RH until dry and the reference mass was recorded.…”
Section: Dynamic Vapour Sorption (Dvs) Analysismentioning
confidence: 99%
“…Increased surface area is a major requirement for mucosal surface adhesion. 29 The marked reduction in particle sizes of the formulation indicates an increase in area-to-volume ratios of the particles; hence the rate of release of the drug from microsphere formulations will also increase. Furthermore, water absorption into smaller particles will be faster because of the shorter distance between the surface and center of the particles; hence there will be an increased rate of swelling.…”
Section: Evaluation Of the Microspheresmentioning
confidence: 99%
“…TRE was chosen for carrier because it is often used as a sweetening or taste masking agent formulated with spray-drying , Pomázi et al, 2011, Moran et al, 2007, Amaro et al, 2015 in pharmaceutical technology.…”
Section: Preformulation Studies Of Tre Based Microcompositesmentioning
confidence: 99%
“…Trehalose is often produced as an excipient by spray-drying Gradon and Sosnowski, 2014;Pomázi et al, 2011;Maurya et al, 2005a;Maurya et al, 2005b;Moran and Buckton, 2007a;Amaro et al, 2015), freeze-drying Jovanovoc et al, 2006;Claus et al, 2011) and spray-freeze-drying (Tonnis et al, 2014;Yu et al, 2006) in pharmaceutical technology. Trehalose tends to undergo amorphization, and the amorphous form is readily prepared by using a solvent method such as spray-or freeze-drying.…”
Section: Introductionmentioning
confidence: 99%